2020
DOI: 10.1159/000512201
|View full text |Cite
|
Sign up to set email alerts
|

Human Acellular Dermal Matrix (Epiflex®) in Immediate Implant-Based Breast Reconstruction after Skin- and Nipple-Sparing Mastectomy and Treatment of Capsular Fibrosis: Results of a Multicenter, Prospective, Observational NOGGO-AWOGyn Study

Abstract: <b><i>Background:</i></b> Over the last decades, the number of acellular dermal matrix (ADM)-assisted implant-based breast reconstructions (IBBR) has substantially increased. However, there is still a lack of prospective data on complication rates. <b><i>Methods:</i></b> We performed a non-interventional, multicenter, prospective cohort study to evaluate complication rates of a human ADM in patients undergoing an IBBR after skin- and nipple-sparing mastectomies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…More data are currently available on their use in breast reconstruction after mastectomy, where ADMs are becoming routinely employed [ 39 ]. However, conflicting data are currently emerging from updated observations of ADM-specific side effects, therefore suggesting careful patient selection for ADM-based reconstructive surgery [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…More data are currently available on their use in breast reconstruction after mastectomy, where ADMs are becoming routinely employed [ 39 ]. However, conflicting data are currently emerging from updated observations of ADM-specific side effects, therefore suggesting careful patient selection for ADM-based reconstructive surgery [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a patient’s perspective, improved quality of life and satisfaction with the surgical result are key outcomes of the breast reconstruction [16]. In our study, in addition to the previously reported complication rates [17], we prospectively assessed patient-reported outcomes, including patient satisfaction and quality of life, in patients who underwent an ADM-assisted immediate breast reconstruction after skin- and nipple-sparing mastectomy with or without prior breast reconstruction. In addition, surgeon satisfaction with the outcome and the aesthetic result judged by 2 independent external experts were assessed.…”
Section: Discussionmentioning
confidence: 99%
“…During follow-up, occurrence of complications, patient satisfaction, surgeon satisfaction, and quality of life (from 1 week after surgery onwards) were assessed and photographs were taken. Details on complication rates in the present study have been reported previously [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation